Misconstructing Characters: A Critical Look at the Translation of the Swearing Words - Deta Maria Sri Darta (TEKNOSASTIK, 2020)
Translating swearing words has become an interesting study to conduct, especially because it involves two different languages that carry different social values. One language might be rich of such words that are considered as taboos, in this case swearing words, others might restrict the use of swearing words. This might create a problem when the swearing words are used as parts of the characterization of a character in a story. As one of the traits, swearing words should be translated as close as possible in order not to distort the character’s quality. This is the task of the translator not to misconstruct the characters in the text s/he translates. This study explores character shift such character distortion due to the translation of swearing words in subtitle translation of a movie, “Suicide Squad” in Indonesian context.